Cumulative impact of multiple evidence based strategies on postnatal growth of extremely-low-birth-weight infants. Issue 6 (June 2021) - Kumar, Praveen; Perino, Jeanne; Bowers, Laura; Welch, Brittany; Albert, Viola; Drenckpohl, Douglas; Wolfe, David
Summary: Background: Postnatal growth failure is common in very preterm infants and is associated with worse neurodevelopmental outcome. Objective: To evaluate the cumulative impact of multiple evidence based strategies on the postnatal growth of extremely-low-birth-weight (ELBW) infants. Methods: We conducted a prospective observational study. Based on current literature, changes were implemented to provide optimal parenteral and enteral nutrition. Daily intakes of calories, protein, lipids and carbohydrates were calculated. The average growth velocity (GV) was calculated using 2-point exponential model and is reported as grams/kg/day. The length and head circumference gains are reported as centimeters/week. Results: The mean gestational age and birth weight for 38 ELBW survivors were 27.0 ± 2.1 weeks and 752 ± 147 g respectively. The GV was 13.2 ± 2.2 g/kg/day (range 8.8–17.4) and gains in length and head circumference were 0.88 ± 0.9 (range 0.15–1.42) and 0.71 ± 0.5 (range 0.22–0.96) centimeters/week respectively. Twenty nine (76.3%) infants were small-for-gestational-age (SGA) at discharge and 23 of these (60.5% of all infants) had weight below 3rd percentile. All 11 infants who were SGA at birth were SGA at discharge as well. Of 25 appropriate-for-gestational-age (AGA) infants at birth, 16 (64%) were SGA at discharge. The number of infants with length and head circumference below 10th percentile at birth and discharge were 11 (28.9%) and 29 (76.3%) for length and 20 (52.6%) and 27 (71.1%) for head circumference. Infants with multiple morbidities and more hospital days with no enteral feeds had lower GV. Conclusion: All infants born SGA at birth and majority of ELBW survivors born AGA at birth had weight, length and head circumference below 10th percentile at discharge despite aggressive nutrition supplementation.